2016
DOI: 10.1186/s12934-016-0562-z
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a microbial coculture of Escherichia coli strains for the biosynthesis of resveratrol

Abstract: BackgroundResveratrol is a plant natural product with many health-protecting effects which makes it an attractive chemical both for academic studies and industrial purposes. However, the low quantities naturally produced by plants as well as the unsustainable procedures of extraction, purification and concentration have prompted many biotechnological approaches to produce this chemical in large quantities from renewable sources. None of these approaches have considered a microbial coculture strategy to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…In fact, the titers of resveratrol produced by C. glutamicum are lower in direct comparison with other already published microbial production strains, but the use of this strain as a platform for polyphenol production is highly appealing for the reasons explained in the Introduction. Further research and development of this strain, aiming at increasing the resveratrol titers, may result in a good platform for industrial resveratrol production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the titers of resveratrol produced by C. glutamicum are lower in direct comparison with other already published microbial production strains, but the use of this strain as a platform for polyphenol production is highly appealing for the reasons explained in the Introduction. Further research and development of this strain, aiming at increasing the resveratrol titers, may result in a good platform for industrial resveratrol production.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of resveratrol that can be obtained from plant cell cultures is at most equal to that reported as naturally occurring in the plant, being the grape cell suspensions ( V. vinifera ) the most promising one, with a resveratrol yield ranging from 2–5 mg L ‐1 . The first studies for microbial resveratrol production reported the use of Saccharomyces cerevisiae and Escherichia coli as cell factories, with a production of around 0.5 g L ‐1 . More recently, other organisms, such as C. glutamicum , which is a workhorse in industrial biotechnology, especially for the production of several aminoacids, proved to be a promising host organisms for resveratrol production .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] This background strain can be further engineered to produce the desired phenylpropanoid CoA esters (such as 4-coumaroyl-CoA) to convert into polyketides. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] A graphical summary of the major pathways targeted in all of these engineering strategies is provided in Figure 2.…”
Section: Escherichia Colimentioning
confidence: 99%
“…[72] This exciting result suggests that further investigation into THN synthases could reveal interesting chemistry, thus further expanding the applications of polyketide production. [95] Escherichia coli Stilbeniod At4CL1, VvSTS Minimal, cerulenin, acid Flask 2.3 g L À1 resveratrol [18] Escherichia coli Stilbeniod Pc4CL, VvSTS matB, matC, RgTAL Minimal, tyr Flask 35 mg L À1 resveratrol [33] Escherichia coli Stilbeniod Pc4CL, VvSTS RgTAL, ΔtyrR ΔtrpED Complex Flask 4.612 mg L À1 resveratrol [30] Escherichia coli Stilbeniod strain 1: Pc4CL, VvSTS strain 2: RgTAL, aroG(fbr), tktA,…”
Section: Minimalmentioning
confidence: 99%